SISTEM INFORMASI MANAJEMEN DATA KLIEN PADA PT. HULU BALANG MANDIRI MENGGUNAKAN FRAMEWORK LARAVEL - Triana Triana; Machudor Yusman; Bambang Hermanto (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The development of technology in modern times is very fast which has an impact on the business outsourcing. Information systems are the most important thing in a company to ensure the quality of information that is fast, precise, and accurate which can support the performance of the company's business processes. Information technology makes access to information very easy and fast. This makes the company able to compete with other companies and have competitive advantages in various things such as company performance and service. Therefore, the existence of an information system has become an absolute necessity for companies in carrying out their business processes. The information system needed in company outsourcing is a client data information system that can manage all information related to partners or potential partners in order to make it easier to obtain information related to clients. With the development of the Client Data Management Information System, it is hoped that it will facilitate PT. Hulu Balang Mandiri in managing client data and making decisions so that the company grows quickly.